Field day on testing several NT seeders - Moussadek, Rachid (2023)
Capacity building, technical and organizational direct seeding takeovers, drawing beneficiaries interested in the subject of training. Participants were very satisfied with the solutions recommended by the facilitators in with regard to the technical management of crops in direct seeding mode